2006
DOI: 10.1038/nature04863
|View full text |Cite
|
Sign up to set email alerts
|

Minimal ProtoHox cluster inferred from bilaterian and cnidarian Hox complements

Abstract: Recent molecular phylogenies support that the non-bilaterian Cnidaria is the sister group to bilaterians (4,5) and are therefore informative to reconstruct the early history of bilaterian homeobox gene complements. Earlier searches for cnidarian homeobox genes have revealed the presence of anterior-like Hox genes as well as Gsx, so that the ProtoHox cluster must have been duplicated prior to the cnidarian-bilaterian split. Earlier reports (6-13) have proposed that posterior Hox genes but not central genes or H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
213
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(231 citation statements)
references
References 20 publications
16
213
2
Order By: Relevance
“…One hypothesis is that hox/parahox clusters originated from the duplication of an ancient protohox cluster with anterior and posterior hox/parahox genes (Brooke et al, 1998;Ferrier and Holland, 2001;Brooke and Holland, 2003;Garcia-Fernandez, 2005a, b). However, other findings propose the protohox cluster may have only consisted of two anterior genes, while the non-anterior genes most probably appeared independently in the hox and parahox clusters after the separation of bilaterians and cnidarians (Chourrout et al, 2006;Kamm et al, 2006). …”
Section: An Ancient Function Of Wnt Signalling In Axial Patterningmentioning
confidence: 94%
See 1 more Smart Citation
“…One hypothesis is that hox/parahox clusters originated from the duplication of an ancient protohox cluster with anterior and posterior hox/parahox genes (Brooke et al, 1998;Ferrier and Holland, 2001;Brooke and Holland, 2003;Garcia-Fernandez, 2005a, b). However, other findings propose the protohox cluster may have only consisted of two anterior genes, while the non-anterior genes most probably appeared independently in the hox and parahox clusters after the separation of bilaterians and cnidarians (Chourrout et al, 2006;Kamm et al, 2006). …”
Section: An Ancient Function Of Wnt Signalling In Axial Patterningmentioning
confidence: 94%
“…However, new data reveal that no complete hox code exists in cnidarians. Although some if not all cnidarians possess a limited number of bilaterian-like anterior hox genes, many of these genes are paralogs and they do not represent equivalents of the hox cluster (Chourrout et al, 2006;Kamm et al, 2006). One hypothesis is that hox/parahox clusters originated from the duplication of an ancient protohox cluster with anterior and posterior hox/parahox genes (Brooke et al, 1998;Ferrier and Holland, 2001;Brooke and Holland, 2003;Garcia-Fernandez, 2005a, b).…”
Section: An Ancient Function Of Wnt Signalling In Axial Patterningmentioning
confidence: 99%
“…Compared with representatives from Bilateria both appear to be relatively derived, whereas the other cnidarian sequence, the Acropora POU3 protein seems to be less derived from the POU consensus. Initial analyses (not shown) with the POU homeodomain alone showed that the Nematostella POU 1, 3 and 4 class genes (Ryan et al, 2006;Chourrout et al, 2006) also seem to be less derived from the POU consensus. However, the homeodomain of the Nematostella POU class 6 gene (Ryan et al, 2006;Chourrout et al, 2006) as well as a putative POU6 gene from Condylactis (with only partial POU S and partial POU H domain) (Shah et al, 2000) show similar deviations as the Eleutheria POU6 homeodomain.…”
Section: Phylogenetic Analyses Of Pou Homeobox Genesmentioning
confidence: 99%
“…Initial analyses (not shown) with the POU homeodomain alone showed that the Nematostella POU 1, 3 and 4 class genes (Ryan et al, 2006;Chourrout et al, 2006) also seem to be less derived from the POU consensus. However, the homeodomain of the Nematostella POU class 6 gene (Ryan et al, 2006;Chourrout et al, 2006) as well as a putative POU6 gene from Condylactis (with only partial POU S and partial POU H domain) (Shah et al, 2000) show similar deviations as the Eleutheria POU6 homeodomain. For example, at homeodomain position 44 all cnidarian class 6 genes show a threonine residue, whereas all other POU genes (including bilaterian class 6) have a valine residue at this position.…”
Section: Phylogenetic Analyses Of Pou Homeobox Genesmentioning
confidence: 99%
See 1 more Smart Citation